The effects of high-intensity interval training on NLRP3 inflammasome and monocyte chemokine receptors in individuals with obesity - Ana Luíza Pereira Assunção Silveira; Daniela Alves de Abreu; Amanda de Lima Santos Musto; Luiz Henrique da Silva Nali; Jônatas Bussador do Amaral; André Luis Lacerda Bachi; Lucas Melo Neves; Saulo Gil; Fernando Mateus Santos; Jefferson Russo Victor; Marina Tiemi Shio; Carolina Nunes França (PLoS ONE, 2026)
Background/ Objectives: Obesity is a chronic disease that promotes increased cytokine production mediated by activating a complex of intracellular proteins known as the inflammasome, mainly NLRP3. The modulation of the NLRP3 inflammasome and monocyte chemokine receptors induced by high-intensity interval training (HIIT) in individuals with obesity is still poorly understood. This training is characterized by a period of high-intensity stimulation followed by a recovery period. The main objective of the current study was to investigate possible modulation of the NLRP3 inflammasome and monocyte chemokine receptors in individuals with obesity following HIIT. Subjects/Methods: In this randomized trial, we included individuals with obesity (n = 109), who have not exercised in the last six months, of both sexes, aged between 18 and 60 years. Interventions: Participants were divided into a trained group, which performed three weekly HIIT sessions over eight weeks, and an untrained group (control). The NLRP3 inflammasome and its components, as well as monocyte chemokine receptors expression were analyzed before and after training period by real-time PCR. Results: Whereas NLRP3 expression were unchanged (p = 0.08), after HIIT there was a decrease in Caspase-1 (CASP-1) expression in contrast to the increase of ASC expression as compared to baseline values (p = 0.04 and p < 0.0001, respectively). Additionally, lower IL-6 expression (p < 0.0001), with no differences in IL-1 β and IL-18 expressions were found after HIIT. Besides, HIIT led to an increase in the expression of CCR2 and CCR5 and a decrease in CX3CR1 expression (p < 0.0001, p = 0.001 and p = 0.007, respectively) compared to baseline. Differentially expressed genes interaction analysis [CASP-1, ASC (PYCARD), IL-6, CCR2, CXC3CR1 and CCR5] revealed interaction with NLRP3 nflammasome genes. Conclusions: Eight weeks of HIIT can modulate some components involved in the NLRP3 inflammasome, as well as monocyte chemokine receptors, in individuals with obesity, suggesting an improvement in the control of inflammatory status. Trial registration : Brazilian Registry of Clinical Trials – ReBEC number RBR-8vfxfqd).